Curating lived Islam in the Muslim world - Malik, Iftikhar Haider, 1949- author.
1 online resource.
Keywords: Beginning with the medieval period, this book collates and reviews first-hand scholarship on Muslims in the Middle East and South Asia, as noted down by eminent British travellers, sleuths and observers of lived Islam. The book foregrounds the pre-colonial and pre-Orientalist phase and locates the multi-disciplinarity of Britain's relationship with Muslims over the last millennium to demonstrate a multi-layered interface. Fully sensitive to a gender balance, the book focuses on specially selected individuals and their transformative experiences while living and working among Muslims. Examining the writings of male and female authors including Adelard, Thomas Coryate, Mary Montagu and Fanny Parkes, the book analyses their understanding of Islam. Moreover, the author explores the works of a salient number of representative colonial British women to move away from the imperious wives stereotype and shed light on gender and Islam in Near East and South Asia by illustrating the status of women, tribal hierarchies, historic and architectural sites and regional politics. Going beyond familiar views about colonialism, travel writings and memsahibs without losing sight of the complex relations between Britain and Asian Muslims, this book will be of interest to academics working on British history, Imperial history, the study of religions, Shi'i Islam, Islamic studies, Gender and the Empire and South Asian Studies.